2012
DOI: 10.1111/j.1553-2712.2012.01306.x
|View full text |Cite
|
Sign up to set email alerts
|

Can Novice Sonographers Accurately Locate an Endotracheal Tube With a Saline‐filled Cuff in a Cadaver Model? A Pilot Study

Abstract: Background: No single confirmatory device can accurately distinguish between endotracheal, endobronchial, and esophageal intubation. Bedside ultrasound (US) shows promising potential for endotracheal tube (ETT) verification. Image acquisition depends on the approach used and the experience of the sonographer. Air within the trachea remains a challenge for interpretation of US images. Insufflation of the ETT cuff with saline helps overcome this difficulty and allows easy visualization of the cuff. This novel ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 9 publications
0
37
0
Order By: Relevance
“…Several other studies, including those using ultrasound or palpation, have revealed that the depth of the ETT was correct when the cuff, rather than the tip, was placed at the sternal notch. 3,4 As MacKay et al did not record the position of the ETT cuff in their study, we are concerned that the cuff may have been too close to the vocal cords, thus increasing the risk of vocal cord impingement as well as unplanned extubation.…”
Section: To the Editormentioning
confidence: 95%
See 1 more Smart Citation
“…Several other studies, including those using ultrasound or palpation, have revealed that the depth of the ETT was correct when the cuff, rather than the tip, was placed at the sternal notch. 3,4 As MacKay et al did not record the position of the ETT cuff in their study, we are concerned that the cuff may have been too close to the vocal cords, thus increasing the risk of vocal cord impingement as well as unplanned extubation.…”
Section: To the Editormentioning
confidence: 95%
“…Several other studies, including those using ultrasound or palpation, have revealed that the depth of the ETT was correct when the cuff, rather than the tip, was placed at the sternal notch. 3,4 As MacKay et al did not record the position of the ETT cuff in their study, we are concerned that the cuff may have been too close to the vocal cords, thus increasing the risk of vocal cord impingement as well as unplanned extubation.We have found it relatively easy to locate the position of the cuff and the vocal cords by ultrasound, and in so doing, if the ETT tip is far enough away from the carina, we can increase the ETT depth to keep the cuff away from the cords. We also agree with the view that subglottic damage by the ETT cuff can be minimized if the upper margin of the cuff is distal to the cricoid cartilage.…”
mentioning
confidence: 95%
“…A more recent report in a cadaver study showed that novice sonographers could accurately identify a saline-inflated ETT cuff at the level of the suprasternal notch. 28 We report temporarily inflating an ETT cuff with saline to directly confirm correct ETT depth during resuscitation.…”
Section: Cjem N Jcmumentioning
confidence: 99%
“…12 Previous reports suggest that inflating the ETT cuff with liquid rather than air (an established and safe practice with applications in many areas of medicine [15][16][17][18][19][20][21][22][23][24][25][26] ) allows the cuff to be visualized on a sonogram. 27,28 An ETT cuff at the level of the suprasternal notch correlates with correct depth of the tip (i.e., just deep to the clavicles. [29][30][31][32] Therefore, sonographic identification of a liquid-filled cuff at the suprasternal notch should confirm the correct depth of intubation.…”
mentioning
confidence: 99%
See 1 more Smart Citation